REDEFINING PULMONARY HYPERTENSION AND EMERGING THERAPEUTIC STRATEGIES - Michał Wabiszczewicz,; Albert Kosarewicz,; Patrycja Krysiak,; Łukasz Woźniak,; Albert Lompart, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: This narrative review summarizes recent advances in the understanding and treatment of elevated pulmonary vascular pressure disorders between 2017 and 2025. Particular emphasis is placed on evolving classification criteria, the emergence of novel therapies, and their impact on clinical practice.Materials and Methods: Rather than presenting a formal systematic search, this review integrates findings from key clinical trials, international guidelines, and major publications indexed in PubMed/MEDLINE, Cochrane Library, Embase, Web of Science, and CINAHL. Special attention is given to studies addressing the role of sotatercept, activin signaling, and the BMP pathway, which have shaped current perspectives.Brief description of the state of knowledge: The past years have witnessed a redefinition of hemodynamic thresholds, lowering the diagnostic criterion for mean pulmonary arterial pressure from ≥25 mmHg to >20 mmHg, enabling earlier diagnosis and broader recognition of disease burden. Epidemiological estimates suggest approximately 192,000 cases worldwide, with a predominance in women. On the therapeutic front, sotatercept represents a landmark advance, acting through the BMP/activin axis and shifting the paradigm toward disease modification. The STELLAR Phase 3 trial demonstrated a 40.8-meter improvement in six-minute walk distance and a 76% reduction in composite adverse outcomes, underscoring its clinical relevance.Summary: Between 2017 and 2025, pulmonary vascular medicine has undergone substantial transformation. The redefinition of diagnostic criteria and the development of sotatercept mark a decisive move from purely symptomatic management toward therapies capable of altering disease progression. These changes not only improve patient prognosis but also redefine future directions in the field.